Synthesis of a Bridged Tetraaza Macrocycle Cu(II) Complex and Its Molecular Magnetic Properties - Bi, Jian-Hong; Bi, Wen-Tao; Hu, Nai-Liang (Asian Journal of Chemistry, 2011)
A novel self-assembled tetraaza macrocycle Cu(II) complex: [(CuL)2Fe(SCN)4](ClO4)2 (L = 5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradeca-4,11-diene) has been synthesized and characterized by IR spectra and elemental analysis. Its molecular magnetic properties investigation shows that weak antiferromagnetic interactions are mediated between the tetraaza macrocycle Cu(II) ions through the [Fe(SCN)4]2- bridged in the complex.